Unfolding the collective functional potential of a synergistic multispecies community through genotypic and phenotypic analyses - Dana Ronin; Mads Frederik Hansen; Maximilian Lukas Flaig; Morten Kam Dahl Dueholm; Anders Ogechi Hostrup Daugberg; Joseph Nesme; Witold Kot; Mette Burmølle (Biofilm, 2025)
By studying model multispecies biofilm systems, we can further our knowledge regarding why some properties emerge solely in a multispecies setting. In this study, the model system under investigation is composed of four bacterial species: Paenibacillus amylolyticus, Microbacterium oxydans, Stenotrophomonas rhizophila and Stenotrophomonas maltophilia. This community was isolated from soil and has previously shown synergistic biofilm formation capabilities in vitro, along with other intrinsic properties, some of which could lead to potential industrial and agricultural applications. In this study, we conducted the first complete genome assemblies for these four strains and performed a manually curated annotation of the genomes to identify genomic features that could guide the selection of relevant phenotypic assays. In all four strains, we identified genes linked to interspecies communication, biofilm formation, secondary metabolite production, antibiotic resistance, enzymatic activity and metabolism of toxic xenobiotics. With metabolism being the largest gene function category identified, we then conducted growth assays on various carbon sources and relevant polysaccharides. This revealed interesting emergent behaviors - regarding growth and enzymatic activity - in the four-species community which were not seen in the monocultures. Overall, analysis of the complete genomes of this model community uncovered gene functions which could play a role in the previously observed community intrinsic properties, as well as provided insight to the positive social interactions observed in vitro.